Genesis and Evolution of the Public in the Russian Empire Under the Conditions of Modernization in the Second Half of the 19th Century - Pokotilova, Tatyana Evgenevna; Miroshnichenko, Nadezhda Viktorovna; Dedyukhina, Irina Fedorovna; Zhdanova, Oksana Viktorovna; Maximov, Vladimir Yurievich (Journal of History Culture and Art Research, 2019)
The article analyzes the factors associated with the history of forming the basics and characteristic features of the phenomenon of the regional public as a constituent part of all-Russian modernization experiments in the second half of the 19th century. It was discovered that in the Stavropol Province, a Southern region of Russia, the evident minimal activity of the overwhelming majority of the population was determined by its peasant composition, the low number and poverty of the nobility and the prevalence of the merchant element in the urban self-government. At the same time, the points of growth were actively manifested through the so-called “newcomers” or nonresidents (those who moved into the region as a result of the abolition of selfdom in Russia and in fact could become full members of the established peasant “world”). These points of growth also included representatives of a number of confessions from those who could potentially, in the course of social development, open up to processes of public association in order to protect their social and cultural interests, having already certain traditions of organized activity, and well-educated population of the urban environment, constantly replenished by the steady development of the education system in the city and in the countryside and united in the framework of legal public organizations to solve various local problems.